Progresywny czy tradycyjny – o postawie normatywnej Andrzeja Glabera z Kobylina w zakresie demorfologizacji rodzaju rzeczownika w formach celownika, narzędnika i miejscownika liczby mnogiej - Migdał, Jolanta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
The article presents a normative attitude of Andrzej Glaber from Kobylin with reference to demorphologization of noun gender in plural of the dative, instrumental and locative case. The forms used by Glaber in his texts were confronted with the linguistic realities observed in Polish paleotypes published in Cracow in 1521-1522, in Polish letters from 1525-1550, in the letters of King Sigismund II Augustus to the Radziwiłs from the years 1547-1572 as well as in the translation of New Testament from The Bible of Brześć from 1563. The results of studies by Wojciech Ryszard Rzepka provide a comparative background, especially the studies focusing on period I, i.e., the years 1521-1535. From the analysed material, it can be gathered that also with regard to three noun cases, which are of interest to us, the progressive attitude of the liberal writer and editor—whom was Andrzej Glaber acting in the first half of the 16th century— was revealed. A great gift of anticipation of development tendencies enabled him to select, from the whole range of alternative endings, the ones which in the further development of the language proved victorious. This selection, sometimes, consisted in preference for definite forms and their domination in texts. Another time, the gist of a progressive attitude was based on precursory introduction, even in small numbers, of the form which only after many years, and even dozens of years, became common and standard in the literary Polish language.